Poly-citrate composite porous bone scaffold and preparation method thereof
By using polycitrate composite porous bone stents loaded with resveratrol and alendronate in bone defect repair materials, the problems of insufficient mechanical properties and poor acidic environment improvement in existing materials in the treatment of critical bone defects are solved, and a significant improvement in bone repair has been achieved.
Patent Information
- Application Number
- CN202510043524.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
The existing bone defect repair materials have problems such as insufficient mechanical properties, poor acidic environment improvement, and low biocompatibility in the treatment of critical bone defects, which are difficult to effectively promote bone repair.
Polycitrate composite porous bone scaffolds were used to load resveratrol and alendronate sodium microspheres in the scaffold, and POCL scaffolds were formed by esterification reactions of citrate and PCL, and a novel bone scaffold with good mechanical properties, hydrophilicity and stability were constructed by covalently combining grafted microspheres.
This bone stent degrades in an acidic environment, releases resveratrol and alendronate sodium, improves the acidic environment, promotes BMSCs proliferation and osteogenesis induction, and significantly improves the bone repair effect.
Smart Images

Figure CN119818725A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field related to medical devices, and in particular to a polycitrate composite porous bone scaffold and a preparation method thereof. Background Art
[0002] Bone defect is one of the most common injuries in clinical practice. Bones themselves have a certain regenerative ability, and most small bone defects do not require surgical intervention. However, bone defects that exceed the critical size threshold are difficult to heal naturally.
[0003] Bone transplantation is the main method for treating bone defects. Currently, bone defect repair materials are mainly divided into three categories: autologous bone, xenogeneic bone and artificial bone repair materials. Among them, autologous bone transplantation is the gold standard for bone repair, but its supply is short and it is easy to cause complications related to the healing of the donor site; xenogeneic bone transplantation can fill large area bone defects, but there are risks such as fibrous nonunion, inflammation and microcrack expansion leading to post-implantation failure. Bone tissue engineering provides a new idea to help solve the problem of bone defects.
[0004] With the rapid development of regenerative medicine and bone tissue engineering, more and better solutions have emerged for the treatment of critical bone defects. At present, engineered biodegradable and non-biodegradable scaffolds can be prepared according to demand to promote bone formation in the defect site. Bone tissue engineering has the following functions: the cell matrix-like framework provides a good three-dimensional microenvironment for seed cells to promote cell adhesion, differentiation and proliferation, as well as various components that promote bone formation. Most of them use small molecules, mesenchymal stem cells, growth factors and the scaffold itself to induce new bone tissue formation. The most basic feature of the scaffold is that it has good biocompatibility in the human body, and some bone implant materials have the ability to permanently fuse with tissues or promote their regeneration.
[0005] The purpose of this application is to propose a new bone repair scaffold material with good mechanical properties, hydrophilicity and stability, which can effectively improve the acidic environment of polycitrate scaffold degradation products, and at the same time has good biocompatibility, can promote the proliferation of BMSCs, and has osteoinductive effect. Summary of the invention
[0006] In view of the deficiencies of the prior art, the present invention provides the following technical solutions:
[0007] A method for preparing a polycitrate composite porous bone scaffold is provided, wherein a novel polycitrate porous bone scaffold loaded with ALN and RSV microspheres is constructed; the method comprises the following steps:
[0008] Step 1: Synthesis of resveratrol calcium carbonate microspheres;
[0009] First, accurately weigh 200 mg of CaCl2·2H2O powder with an electronic scale, pour it into 100 mL of anhydrous ethanol and ultrasonically dissolve it for later use; then weigh 100 mg of resveratrol powder and dissolve it in 100 mL of anhydrous ethanol for later use; according to the molar mass of resveratrol in the system of 1:1, about 17.5 mg of NaOH particles are dissolved in 50 mL of anhydrous ethanol and ultrasonically dissolved; the ultrasonicated NaOH anhydrous ethanol solution and the resveratrol anhydrous ethanol solution are poured into a 250 mL glass beaker and mixed evenly; the solution is clear and uniform with a yellowish green color, which means that the resveratrol is fully ionized;
[0010] Then slowly add anhydrous ethanol solution of CaCl2·2H2O into the beaker, seal the beaker with a sealing film and poke several small holes with a diameter of 2-3mm on the sealing film to connect it to the outside world, put the beaker in a dry glass dish, put excess ammonium bicarbonate powder at the bottom of the dish, apply vaseline to the mouth of the dry glass dish to keep the bottle airtight, and then use an oil-free diaphragm vacuum pump to make the dry glass dish a vacuum negative pressure state; and put the dry glass dish in an electric blast drying oven, set at 37℃, and let it stand in the dark for 4-5 days, then CaCO3 precipitation can be found in the beaker.
[0011] Finally, the precipitate was placed in a desktop large-capacity centrifuge at 2000 rpm. After 10 minutes, the supernatant was discarded and washed with anhydrous ethanol. After repeating the centrifugal washing three times, a calcium carbonate microsphere precipitate was obtained. The precipitate was placed in a vacuum freeze dryer for 48 hours to obtain resveratrol calcium carbonate microsphere powder, which was stored in a -20°C refrigerator away from light.
[0012] Step 2: Preparation of resveratrol microspheres-alendronate sodium / polycitrate scaffold (POCL / ALN / RSV); wherein citric acid powder and 1,8-octanediol particles account for 50%, resveratrol microspheres account for 30%, and PCL-80000 accounts for 20%;
[0013] First, citric acid powder and 1,8-octanediol particles were weighed in a 1:1 molar mass ratio in a polytetrafluoroethylene beaker and mixed, placed in an oil bath at 140°C, heated with N2, and stirred at 300 rpm / min;
[0014] After all the alendronate trihydrate particles are dissolved, add them, react for 15 minutes, add the corresponding proportion of PCL-80000 and continue to stir and react. After 0.5 hours, slowly add a certain proportion of resveratrol calcium carbonate microspheres several times and continue to react for 1 hour. After 0.5 hours, when the cross-linking degree of the polymer increases and gradually becomes viscous, stop stirring and continue heating and reacting. After 6-8 hours, the scaffold begins to take shape and stop the reaction.
[0015] Finally, demould it from the polytetrafluoroethylene beaker, put it into a vacuum drying oven at 90°C, continue heating and drying for 72 hours away from light, take it out, put it into a refrigerator at 4°C to dry and store it away from light.
[0016] Furthermore, the polycitrate composite porous bone scaffold prepared by the above preparation method is used in the treatment and preparation of bone defect repair materials.
[0017] Compared with the prior art, the technical solution of this application has the following beneficial effects:
[0018] The present invention utilizes citric acid and 1,8-octanediol to prepare polycitrate by thermal cross-linking at high temperature, then adds PCL to undergo esterification reaction to synthesize polycaprolactone-citrate (POCL), and then covalently binds ALN and RSV-loaded calcium carbonate microspheres prepared by co-precipitation of calcium chloride dihydrate and ammonium bicarbonate to the POCL scaffold; RSV-loaded calcium carbonate microspheres are successfully prepared, and the microspheres can degrade and release RSV in an acidic environment, and a novel polycitrate porous bone scaffold loaded with ALN and RSV microspheres is successfully constructed, the scaffold has good mechanical properties, hydrophilicity and stability, can effectively improve the acidic environment of the degradation product of the polycitrate scaffold, and the scaffold has good biocompatibility, can promote the proliferation of BMSCs, has an osteogenic induction effect, and thus promotes bone repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 TEM images of resveratrol calcium carbonate microspheres (where A, B, C, and D are transmission electron microscope images of resveratrol calcium carbonate microspheres with scalebar = 10 μm, 5 μm, 1 μm, and 500 nm, respectively);
[0020] Figure 2 It is the UV-visible absorption spectra of resveratrol and resveratrol calcium carbonate microsphere solution;
[0021] Figure 3 FT-IR spectrum of POCL / ALN / RSV scaffold;
[0022] Figure 4 The thermogravimetric analysis results of RSV microspheres, POCL scaffolds, ALN scaffolds and RSV scaffolds are shown;
[0023] Figure 5 Photos and scanning electron microscope images of POCL, POCL / ALN, POCL / ALN / RSV (A is a photo of POCL, POCL / ALN, POCL / ALN / RSV, B, C, D are scanning electron microscope images of POCL, POCL / ALN, POCL / ALN / RSV with Scalebar = 500 μm, E, F, G are scanning electron microscope images of POCL, POCL / ALN, POCL / ALN / RSV with Scalebar = 100 μm);
[0024] Figure 6 The mechanical properties test diagram of POCL, POCL / ALN, and POCL / ALN / RSV stents;
[0025] Figure 7 These are the water drop angle test diagrams of POCL, POCL / ALN, and POCL / ALN / RSV (A, B, and C are the water drop angle test diagrams of POCL, POCL / ALN, and POCL / ALN / RSV, respectively; and D is the water drop angle-time variation diagram of POCL, POCL / ALN, and POCL / ALN / RSV);
[0026] Figure 8 The degradation efficiency diagram of POCL, POCL / ALN, and POCL / ALN / RSV scaffolds in PBS and MES buffers;
[0027] Fig. 9 Biocompatibility test diagrams of POCL, POCL / ALN, and POCL / ALN / RSV (A, B, C, and D are cell live and dead staining diagrams of BMSCs in the blank group after co-culture with POCL, POCL / ALN, and POCL / ALN / RSV for 48 hours, E is a CCK-8 cell proliferation test diagram of BMSCs in the blank group after co-culture with POCL, POCL / ALN, and POCL / ALN / RSV for 24 hours, and F is a color change diagram of POCL, POCL / ALN, and POCL / ALN / RSV of the same quality placed in the same volume of basal culture medium containing phenol red for 24 hours);
[0028] Fig.10 ALP detection of osteogenic induction of POCL, POCL / ALN, and POCL / ALN / RSV scaffolds (A, B, C, and D are alkaline phosphatase staining images of BMSCs in the blank group after co-culture with POCL, POCL / ALN, and POCL / ALN / RSV scaffolds for one week, respectively);
[0029] Fig.11 Graphs showing the effects of POCL, POCL / ALN, and POCL / ALN / RSV scaffolds on cell cycle (A is a graph showing the cell cycle of BMSCs detected by flow cytometry under blank treatment, B is a graph showing the cell cycle of BMSCs detected by flow cytometry under osteogenic induction medium treatment, C is a graph showing the cell cycle of BMSCs detected by flow cytometry under osteogenic induction medium POCL co-culture treatment, D is a graph showing the cell cycle of BMSCs detected by flow cytometry under osteogenic induction medium POCL / ALN co-culture treatment, and E is a graph showing the cell cycle of BMSCs detected by flow cytometry under osteogenic induction medium POCL / ALN / RSV co-culture treatment). DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Embodiment 1:
[0032] A method for preparing a polycitrate composite porous bone scaffold comprises the following steps:
[0033] Step 1: Synthesis of resveratrol calcium carbonate microspheres;
[0034] First, accurately weigh 200 mg of CaCl2·2H2O powder with an electronic scale, pour it into 100 mL of anhydrous ethanol and ultrasonically dissolve it for later use; then weigh 100 mg of resveratrol powder and dissolve it in 100 mL of anhydrous ethanol for later use; according to the molar mass of resveratrol in the system of 1:1, about 17.5 mg of NaOH particles are dissolved in 50 mL of anhydrous ethanol and ultrasonically dissolved; the ultrasonicated NaOH anhydrous ethanol solution and the resveratrol anhydrous ethanol solution are poured into a 250 mL glass beaker and mixed evenly; the solution is clear and uniform with a yellowish green color, which means that the resveratrol is fully ionized;
[0035] Then slowly add anhydrous ethanol solution of CaCl2·2H2O into the beaker, seal the beaker with a sealing film and poke several small holes with a diameter of 2-3mm on the sealing film to connect it to the outside world, put the beaker in a dry glass dish, put excess ammonium bicarbonate powder at the bottom of the dish, apply vaseline to the mouth of the dry glass dish to keep the bottle airtight, and then use an oil-free diaphragm vacuum pump to make the dry glass dish a vacuum negative pressure state; and put the dry glass dish in an electric blast drying oven, set at 37℃, and let it stand in the dark for 4-5 days, then CaCO3 precipitation can be found in the beaker.
[0036] Finally, the precipitate was placed in a desktop large-capacity centrifuge at 2000 rpm. After 10 minutes, the supernatant was discarded and washed with anhydrous ethanol. After repeating the centrifugal washing three times, a calcium carbonate microsphere precipitate was obtained. The precipitate was placed in a vacuum freeze dryer for 48 hours to obtain resveratrol calcium carbonate microsphere powder, which was stored in a -20°C refrigerator away from light.
[0037] Step 2: Preparation of resveratrol microspheres-alendronate sodium / polycitrate scaffold (POCL / ALN / RSV); citric acid powder and 1,8-octanediol particles account for 50%, resveratrol microspheres account for 30%, and PCL-80000 accounts for 20%;
[0038] First, citric acid powder and 1,8-octanediol particles were weighed in a 1:1 molar mass ratio in a polytetrafluoroethylene beaker and mixed, placed in an oil bath at 140°C, heated with N2, and stirred at 300 rpm / min;
[0039] After all the alendronate trihydrate particles are dissolved, add them, react for 15 minutes, add the corresponding proportion of PCL-80000 and continue to stir and react. After 0.5 hours, slowly add a certain proportion of resveratrol calcium carbonate microspheres several times and continue to react for 1 hour. After 0.5 hours, when the cross-linking degree of the polymer increases and gradually becomes viscous, stop stirring and continue heating and reacting. After 6-8 hours, the scaffold begins to take shape and stop the reaction.
[0040] Finally, the mold was removed from the polytetrafluoroethylene beaker, placed in a vacuum drying oven at 90°C, and heated and dried for 72 hours in the dark. The mold was taken out and placed in a refrigerator at 4°C for drying and stored in the dark. Citric acid-polycaprolactone POCL and citric acid-polycaprolactone-sodium alendronate POCL / ALN scaffolds were prepared by thermal polymerization with the same mass.
[0041] It should be noted that, in this embodiment, poly 1,8-octanediol citrate (POC) is a biodegradable elastomer made of citric acid, which has good mechanical properties and degradation properties. And the polymer surface is easy to functionalize; Polycaprolactone (PCL) has good biocompatibility, completely degrades into water and CO2, and is widely used in orthopedics, radiology, rehabilitation and other medical fields as a medical external fixation material; 1,8-octanediol and citric acid are melt-polycondensed in situ under PCL, and POCL bioelastomer is obtained after curing. Due to the introduction of PCL long-chain molecules, the tensile deformation ability of polycitrate elastomer is improved, and the processing performance of the prepolymer is also improved to a certain extent; Resveratrol RSV is a small molecule extracted from plants, which has anti-inflammatory, antioxidant, anti-osteoporosis and other effects. It has been recently discovered that RSV has the function of phytoestrogen, which can promote the osteogenic differentiation of various stem cells and the formation of blood vessels, but the mechanism of resveratrol affecting the osteogenic differentiation of bone marrow mesenchymal stem cells has not been fully explored. RSV promotes bone formation at 5-25μM. When the RSV concentration exceeds 25μM, it will initiate cell apoptosis. Therefore, the sustained release of RSV becomes a difficult problem that needs to be solved. Alendronate sodium ALN belongs to the bisphosphonate drug and is currently the most widely used drug for the treatment of osteoporosis. Studies have shown that ALN prevents bone loss and osteoporosis by initiating osteoclast apoptosis. Currently, ALN is mainly taken orally, and the absorption efficiency of bisphosphonates in the body is extremely low. Studies have shown that the absorption rate of alendronate sodium in the gastrointestinal tract is only about 0.7%.
[0042] In this embodiment, CaCO3 microspheres encapsulating resveratrol were prepared. Compared with chitosan microspheres, calcium carbonate microspheres have high heat resistance and stability, which facilitates us to prepare POCL / ALN / CA-RSV composite scaffolds through thermal cross-linking reaction in the future, so as to repair critical bone defects; the main component POCL introduces citric acid on the basis of PCL, so it has better hydrophilicity. On the one hand, cells adhere and grow on the scaffold; ALN forms an amide bond with -NH2 and -COOH on the citrate, on the one hand, neutralizes part of the -COOH to improve the acidity and alkalinity of the scaffold, and on the other hand, it can be slowly degraded by lipase in the body to achieve a sustained release effect; the prepared calcium carbonate microspheres are used to encapsulate resveratrol. On the one hand, calcium carbonate can cross-link and neutralize part of the -COOH to improve the problem of over-acidity of the scaffold, and the H released in the subsequent scaffold degradation process can effectively improve the stability of the scaffold. + It can react with the microspheres to degrade the microspheres and release the resveratrol encapsulated therein, thereby achieving the ability of sustained release of resveratrol, preventing the cytotoxicity caused by excessive local resveratrol concentration, and providing a good microenvironment for the bone defect site, thereby achieving the purpose of treating critical bone defects; it provides a new treatment strategy for the repair of critical bone defects; this study focuses on the application of resveratrol and alendronate sodium sustained-release composite polycitrate scaffolds. After improving the performance of the polycitrate scaffold, the inflammatory microenvironment is improved by sustained-release resveratrol. Resveratrol and alendronate sodium coordinately induce the directional differentiation of bone marrow mesenchymal stem cells, thereby promoting the adhesion and proliferation of osteoblasts, and achieving the purpose of repairing critical bone defects.
[0043] Embodiment 2:
[0044] According to Example 1, this example is the identification and characterization of resveratrol calcium carbonate microspheres:
[0045] Weigh 20 mg of resveratrol calcium carbonate microsphere powder and 20 mg of resveratrol powder, prepare 5% HCl anhydrous ethanol solution to dissolve the microspheres and resveratrol, let stand for 5 minutes and wait for CO2 to overflow, take 0.2 mL of each solution into a quartz ELISA plate, and measure the sample's absorption spectrum at 200-400 nm in an ELISA instrument; and prepare part of the resveratrol calcium carbonate microsphere powder into a transmission electron microscope sample to detect the particle size and shape;
[0046] like Figure 1 As shown, the resveratrol microsphere powders washed with anhydrous ethanol and then freeze-dried were subjected to TEM scanning and found that the microspheres were uniform in size and calcium carbonate microspheres encapsulating RSV ( Figure 1 A and B in the figure are composed of nanoparticles of uniform size and diameter of about 100 nm ( Figure 1 C, D in );
[0047] like Figure 2As shown, the RSV microspheres were subsequently dissolved in a mixed solution of MES and anhydrous ethanol (1:1) at pH = 5.5 and a solution of PBS and anhydrous ethanol (1:1) at pH = 7.4, and a spectral scan of 230nm-400nm was performed. It was found that the absorbance of the resveratrol calcium carbonate microspheres in the PBS solution of pH = 7.4 had no significant change, but the absorbance at 300nm in the mixed solution of MES and anhydrous ethanol (1:1) at pH = 5.5 had a significant increase, and was similar to the curve of the anhydrous ethanol solution of pure RSV, proving that RSV was successfully encapsulated and showed the characteristics of release under acidic conditions;
[0048] Embodiment 3:
[0049] According to Example 1, this example is the characterization of polycitrate scaffolds (POCL, POCL / ALN and POCL / ALN / RSV):
[0050] like Figure 3 As shown in the figure, after synthesizing the microspheres, three scaffolds, POCL, POCL / ALN, and POCL / ALN / RSV, were synthesized by thermal polymerization, and the prepolymers of 1,8-OC, CA, PCL, ALN, RSV / RSV microspheres and the three scaffolds were scanned by Fourier transform infrared spectrometer; it was found that the polymer POC had the absorption peaks of -C(=O)O2- of CA and -CH2- of 1,8-OC at around 1705nm and 2932nm, proving that CA and 1,8-OC were successfully prepared into poly 1,8-octanediol citrate, and CO3 2- CO bonds, and the Ca in calcium carbonate also appeared at 870nm 2+ The characteristic vibration peaks of O atoms prove that RSV calcium carbonate microspheres are successfully grafted onto the POCL scaffold;
[0051] like Figure 4 As shown, it was found that the thermal decomposition diagram of POCL / ALN / RSV scaffold and RSV microspheres showed that the mass proportion of RSV microspheres in POCL / ALN / RSV scaffold was about 30%, which was consistent with the proportion in material synthesis;
[0052] like Figure 5 As shown, the synthesized scaffold was placed in a vacuum drying oven and cross-linked at 90°C for 72 hours. After cutting the scaffold samples with uniform shapes, it was observed using a scanning electron microscope and the naked eye that the POCL scaffold formed a transparent scaffold with a high degree of polymerization and a tough texture. The POCL / ALN / RSV scaffold was observed by the naked eye and SEM ( Figure 6 A, D, and G in the figure all form porous structures. The POCL / ALN scaffold is not obvious to the naked eye, but the formation of pores can be observed under the field of view of 500 μm ( Figure 6C and D in the figure). Compared with POCL, POCL / ALN and POCL / ALN / RSV, the two stents have a better surface area / volume ratio and greater advantages in degradation performance;
[0053] like Figure 6 As shown, the scaffold was cut into cubes and the compressive mechanical properties of the scaffold were tested. The force required for the scaffold compression strain range of 0-50% was uniformly measured, and the compressive stress-strain relationship diagram was measured by calculation. The compressive stress of POCL in the range of 0-50% is 127.19N, and the corresponding compressive stress is 1.27MPa; the compressive stress of POCL / ALN in the range of 0-50% is 51.84N. The corresponding compressive stress is 0.43MPa; the maximum compressive stress of POCL / ALN / RSV in the range of 0-50% is 438.69N. The corresponding compressive stress is 3.75MPa. The mechanical properties of POCL / ALN are the weakest, but after adding RSV calcium carbonate microspheres, the mechanical properties are significantly improved to the level of bioceramics. Compared with the other two scaffolds, the mechanical properties are more in line with the requirements of load-bearing bone defects;
[0054] like Figure 7 As shown in the figure, the water drop angle test instrument was used to detect the hydrophilicity and hydrophobicity of the three scaffolds. It was found that the average water drop angle of POCL / ALN was the smallest within 0-60s, which was significantly improved compared with POCL. The hydrophilicity of POCL / ALN / RSV scaffold was between that of POCL scaffold and POCL / ALN / RSV scaffold, but compared with PCL, all three had good hydrophilic properties to facilitate cell adhesion.
[0055] like Figure 8 As shown in the figure, the scaffold was subjected to degradation test, in which the degradation rate of the scaffold in PBS was slow overall, with the rate of POCL / ALN>POCL>POCL / ALN / RSV. The overall degradation of the scaffold showed a trend of slow first and then fast, but the overall degradation rate was still stable. After 12 weeks, the degradation rate of POCL / ALN was about 39%; the degradation rate of POCL was about 24%; and the degradation rate of POCL / ALN / RSV scaffold was only 14%. Subsequently, according to the simulated in vivo bone defect inflammatory environment, the degradation rate of the scaffold was improved by placing it in MES solution with pH = 5.5, and the degradation rate of POCL / ALN / RSV increased from 14% to 19%, and the degradation rates of POCL and POCL / ALN increased to 35% and 44%, respectively. The scaffold is more easily degraded in an acidic environment and can play a more effective role in the acidic microenvironment of bone defects.
[0056] Embodiment 4:
[0057] According to Example 1, this example is a test of the biocompatibility and cytotoxicity of the scaffold in vitro. Fig. 9 As shown, when the cell density is above 80%, the same mass of POCL / ALN / RSV, POCL, and POCL / ALN scaffolds are co-cultured for 48 hours and LiveDead staining is performed. It can be found that the cell density of the POCL scaffold is significantly ( Fig.10 B) was lower than the other three groups, and a large number of dead cells labeled with PI red fluorescence could be observed. The cell density in the POCL / ALN / RSV scaffold group was the highest; there was no obvious toxicity in the POCL and POCL / ALN groups.
[0058] Finally, the CCK8 kit was used to detect the absorbance of the culture medium at 450nm after 24h of co-culture with the scaffold. Compared with the CON group, the cell viability of POCL was still significantly lower than that of the other two groups ( Fig. 9 E). Due to the strong acidity of citric acid in POCL, we put the three scaffolds of the same mass, POCL, POCLALN, and POCL / ALN / RSV, into the same volume of culture medium containing phenol red and found that the culture medium containing POCL scaffold turned yellow obviously, while POCLALN and POCL / ALN / RSV did not change significantly, indicating that the POCL group released a large amount of H + , resulting in a decrease in the pH value of the solution. The reduction in POCL / ALN toxicity may be because the addition of ALN consumes the excess acidic carboxyl groups on POCL. POCL / ALN / RSV has calcium carbonate microspheres. During the preparation process, the excess carboxyl groups will combine with the calcium carbonate microspheres. In addition, the POCL material degrades into acidic components such as citric acid in the body, which can also be absorbed by the calcium carbonate material and release RSV at the same time. Therefore, the POCL / ALN / RSV material is a degradable material that can regulate the acidity of injured tissues in the body.
[0059] Embodiment 5:
[0060] According to Example 1, this example is to detect the effect of the scaffold on BMSCs ALP, such as Fig.10 As shown in the figure, POCL, POCL / ALN, POCL / ALN / RSV of the same mass were co-cultured with BMSCs under osteogenic induction conditions for 7 days, the medium was changed every 24 hours, and BCIP / NBT alkaline phosphatase staining was performed using a kit. The results were observed under the naked eye and white light microscope, and it was found that ( Fig.10 ) The enzyme activity of ALP in the co-culture of POCL / ALN / RSV scaffolds was higher than that of the OB group and higher than that of the POCL and POCL / ALN groups. The ALP content in the POCL scaffold group was the lowest. In addition, the cell morphology of the POCL / ALN / RSV group began to change to some extent, indicating differentiation toward osteoblasts, proving that the POCL / ALN / RSV scaffold can accelerate the induction of osteogenic differentiation to a certain extent.
[0061] Embodiment 6:
[0062] According to Example 1, this example is the effect of the scaffold on the cell cycle of BMSCs. Fig.11 As shown, using the cell cycle detection kit, the diploid content can be detected in the flow cytometer to determine which stage the cells are in. ( Fig.11 ) It can be found that the G2 / M period of the POCL / ALN / RSV scaffold co-culture group was significantly higher than that of other groups, whether compared with blank induction or osteogenic induction. This proves that POCL / ALN / RSV can increase cell division when co-cultured with BMSCs.
[0063] Embodiment 7:
[0064] According to Examples 1-7, three POC-based scaffolds were prepared: POCL, POCL / ALN, and POCL / ALN / RSV. First, as a citric acid-based polymer, POCL shows obvious acidity in material characterization. Citric acid is an intermediate product of metabolism in the body. Under normal circumstances, citric acid can only play its role after entering the mitochondria. As tissues in the body, especially cells, need to live in a suitable pH range to carry out normal physiological activities. Studies have shown that common fractures cause bone defects to be in a highly acidic, hypoxic microenvironment, and the acidic environment will seriously affect the expression of osteogenesis-related factors such as ALP, OPN and COL-1, thereby slowing down bone repair and healing. The degradation rate of the POCL scaffold in an acidic environment will also be accelerated, further leading to a lower local pH.
[0065] After the introduction of RSV microspheres, POCL / ALN / RSV scaffolds have a certain degree of acid resistance. In the process of treating POCL series materials with culture medium containing phenol red, it can be found that although the acidity of some scaffolds of POCL and POCL / ALN was improved by vacuum thermal polymerization later, POCL / ALN / RSV had a more obvious improvement than the other two, which is consistent with the addition of calcium carbonate. 2+ The introduction consumed a lot of H + , and Ca 2+ It also plays a very important role in bone differentiation.
[0066] In the initial design, we gave priority to encapsulating RSV in Ca3(PO4)2 microspheres, because calcium phosphate and hydroxyapatite are both calcium phosphate salts, which are more in line with the composition requirements of original bone in the preparation of bone tissue engineering scaffolds. However, we finally chose to prepare resveratrol microspheres encapsulated by calcium carbonate. Considering the release of RSV during scaffold degradation, calcium phosphate is more difficult to decompose in the acidic microenvironment of bone defects than calcium carbonate, and RSV is difficult to be released by the scaffold. On another level, studies have also shown that in POC scaffolds containing hydroxyapatite, the complete degradation and metabolism of the scaffold takes up to two years. Therefore, calcium carbonate with better degradation performance was finally selected. Studies have also shown that calcium carbonate is absorbed faster than β-tricalcium phosphate with similar structure, which can reduce the impact of the slow degradation rate of calcium phosphate. In addition, Ca in calcium carbonate 2+ More easily released, calcium carbonate plays a supporting role in the functioning of osteogenic precursor cells.
[0067] In the final mechanical properties test, it was also found that the POCL scaffold can form a dense porous structure after the incorporation of ALN molecules, but it also led to a decrease in mechanical properties. However, after the incorporation of RSV microspheres, this problem was solved. Finally, the compressive stress of the POCL / ALN / RSV scaffold can reach more than 4.0MPa, and it has certain support performance. In addition, porous rigid scaffolds have greater advantages in transmitting mechanical stress, and mechanical stress also plays an important role in regulating the proliferation and differentiation of stem cells. And because of the generation of a porous structure, due to the increase in surface area / volume, there is more contact space, both the cell adhesion ability and degradation ability have been improved to a certain extent, which can be reflected in the degradation of PBS and MES buffer solutions.
[0068] Finally, it was found that the POCL / ALN / RSV scaffold can improve the osteogenic differentiation function of BMSCs in vitro and promote bone regeneration in vivo. However, it was also found in vivo that compared with POCL and POCL / ALN, the degradability of POCL / ALN / RSV was worse, and to a certain extent, it could achieve the effect of sustained release of RSV acid resistance.
[0069] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a polycitrate composite porous bone scaffold, characterized in that: A novel polycitrate porous bone scaffold loaded with ALN and RSV microspheres was constructed; the method comprises the following steps: S1: Dissolve resveratrol and NaOH particles in anhydrous ethanol at an equal molar mass ratio, then pour the ultrasonicated NaOH anhydrous ethanol solution and the resveratrol anhydrous ethanol solution into a beaker and mix them to fully ionize resveratrol; S2: Slowly add CaCl2·2H2O anhydrous ethanol solution into the beaker, seal the beaker with a sealing film and poke several small holes in the sealing film to connect it to the outside, put the beaker into a dry glass dish, put excess ammonium bicarbonate powder at the bottom of the dish, and make the glass dish in a vacuum negative pressure state; S3: Place the dry glass dish in an electric blast drying oven, and after standing and avoiding light, CaCO3 precipitation can be found in the beaker; centrifuge the precipitation and discard the supernatant, then wash with anhydrous ethanol, repeat the centrifugation and washing 3 times to obtain calcium carbonate microsphere precipitation, place the precipitation in a vacuum freeze dryer for 48 hours, and obtain resveratrol calcium carbonate microsphere powder, which is stored in the dark; S4: Weigh citric acid powder and 1,8-octanediol particles in an equimolar mass ratio and mix them in a polytetrafluoroethylene beaker, place them in an oil bath, and heat and stir them with N2; add alendronate trihydrate particles after they are completely dissolved, and after the reaction, add a corresponding proportion of PCL-80000 and continue to stir and react, then slowly add a certain proportion of resveratrol calcium carbonate microsphere powder several times to continue the reaction, stop stirring when the polymer cross-linking degree increases and gradually becomes viscous, continue heating and reacting until the scaffold begins to take shape and stop the reaction; S5: De-mold from the polytetrafluoroethylene beaker, put into a vacuum drying oven, continue heating and drying in the dark, then take out to obtain a novel polycitrate porous bone scaffold loaded with ALN and RSV microspheres, and store in a refrigerator to dry and avoid light.
2. The method for preparing a polycitrate composite porous bone scaffold according to claim 1, characterized in that: The specific steps in S1 are as follows: S1.1: Weigh 100 mg of resveratrol powder and dissolve it in 100 mL of anhydrous ethanol for later use; S1.2: Dissolve about 17.5 mg of NaOH pellets in 50 mL of anhydrous ethanol in a 1:1 ratio of the molar mass of resveratrol in the system by ultrasonication; S1.3: Pour the ultrasonicated NaOH anhydrous ethanol solution and the resveratrol anhydrous ethanol solution into a 250 mL glass beaker and mix evenly. If the solution is clear and uniform with a yellowish green color, it means that the resveratrol is fully ionized.
3. The method for preparing a polycitrate composite porous bone scaffold according to claim 1, characterized in that: The specific steps in S2 are as follows: S2.1: Weigh 200 mg of CaCl2·2H2O powder, pour it into 100 mL of anhydrous ethanol and dissolve it by ultrasonication, then slowly add the anhydrous ethanol solution of CaCl2·2H2O into the beaker; S2.2: Seal the beaker with a sealing film and make several holes with a diameter of 2-3 mm on the sealing film to connect it to the outside world; S2.3: Place the beaker in a dry glass dish, put excess ammonium bicarbonate powder at the bottom of the dish, and apply vaseline to the mouth of the dry glass dish to keep the bottle airtight; then use an oil-free diaphragm vacuum pump to create a vacuum negative pressure state in the dry glass dish.
4. The method for preparing a polycitrate composite porous bone scaffold according to claim 1, characterized in that: The specific steps in S3 are as follows: S3.1: Place the dry glass dish in an electric blast drying oven at 37°C and leave it in the dark for 4-5 days. CaCO3 precipitation can be found in the beaker. S3.2: Place the precipitate in a desktop large-capacity centrifuge at 2000 rpm for 10 min, discard the supernatant, and then wash with anhydrous ethanol. Repeat the centrifugation and washing three times to obtain the calcium carbonate microsphere precipitate; S3.3: Place the precipitate in a vacuum freeze dryer for 48 hours to obtain resveratrol calcium carbonate microsphere powder, which should be stored in a -20°C refrigerator away from light.
5. The polycitrate composite porous bone scaffold and preparation method according to claim 1, characterized in that: In the S4, citric acid powder and 1,8-octanediol particles account for 50%, resveratrol microspheres account for 30%, and PCL-80000 accounts for 20%. The specific steps are as follows: S4.1: Weigh citric acid powder and 1,8-octanediol particles in a 1:1 molar mass ratio in a polytetrafluoroethylene beaker, mix well, place in an oil bath at 140°C, heat with N2, and stir at 300 rpm / min; S4.2: After all the alendronate trihydrate particles are dissolved, add them, react for 15 minutes, add 20% of the total PCL-80000 and continue stirring to react; S4.3: After 0.5 hours, slowly add resveratrol calcium carbonate microspheres with a total proportion of 30% several times and continue to react for 1 hour. After 0.5 hours, when the polymer cross-linking degree increases and gradually becomes viscous, stop stirring and continue heating to react. After 6-8 hours, the scaffold begins to take shape and the reaction is stopped.
6. The polycitrate composite porous bone scaffold and preparation method according to claim 1, characterized in that: The S5 was demoulded from the polytetrafluoroethylene beaker, placed in a vacuum drying oven at 90°C, and heated and dried for 72 hours in the dark, then taken out and placed in a refrigerator at 4°C for drying and storage in the dark.
7. A polycitrate composite porous bone scaffold prepared according to the preparation method according to any one of claims 1 to 6.
8. Use of the polycitrate composite porous bone scaffold prepared by the preparation method according to any one of claims 1 to 6 in treating and preparing bone defect repair materials.